2019
DOI: 10.3889/oamjms.2019.649
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Asthma Control with Quality of Life among a Sample of Egyptian Asthmatic School Children

Abstract: BACKGROUND:Asthma is considered a chronic health illness that not only resulted in physical symptoms but also emotional effects. It is; therefore, so important to assess the quality of life of asthmatic patients besides their level of disease control.AIM:To determine the correlation of asthma control with the health-related quality of life (HRQOL) of asthmatic children in Egypt.METHODS:One hundred and twenty-eight asthmatic Egyptian children were enrolled in the study. They were subjected to asthma severity gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
5
1
1
Order By: Relevance
“…It was coincided with Banjari et al [28] who reported that only [16%] control rate in his studied asthmatic children. It was different from previous study who reported that [40.6%] of asthmatic children had controlled level of asthma [29] .…”
Section: Asthma Control and Comorbid Conditionscontrasting
confidence: 87%
See 1 more Smart Citation
“…It was coincided with Banjari et al [28] who reported that only [16%] control rate in his studied asthmatic children. It was different from previous study who reported that [40.6%] of asthmatic children had controlled level of asthma [29] .…”
Section: Asthma Control and Comorbid Conditionscontrasting
confidence: 87%
“…It also implies that an asthmatic youngster needed both medical care and mental counseling. Elnady et al [29] noted in the same context that there was no significant difference in the emotional function score between the two asthmatic groups [controlled and uncontrolled].…”
Section: Asthma Control and Pediatric Asthma Quality Of Lifementioning
confidence: 99%
“…Asthma control is directly linked to a patient’s physical and emotional capability and their QoL [ 25 , 26 ]. Another study from Egypt revealed that asthmatic children and adolescents with controlled asthma had higher PAQoL scores than their counterparts with uncontrolled asthma [ 27 ]. Garina et al conducted a study on Indonesian asthmatic adolescents aged 12–14 years old.…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL was estimated among the asthmatic Egyptian children before but none of the studies used the EQ-5D-Y questionnaire. [10][11][12][13] Healthy children might have their quality of life affected owing to several factors including multidimensional poverty, crowdedness and multiple deprivations related to lack of access to services and support mechanisms. It is estimated that 28% of Egyptians are living below the national monetary poverty line.…”
Section: Discussionmentioning
confidence: 99%